DROPLET INTERFACES IN ELECTRO-WETTING DEVICES - HOLDEN MATTHEW; WHITE JAMES; HERON ANDREW JOHN; CLARKE JAMES ANTHONY; ANDERSON SALLY; HYDE JASON ROBERT; HADWEN BENJAMIN JAMES (2024)
액적 계면은 구동 전극들의 어레이를 포함하는 전기-습윤 소자 내의 액적들 사이에 형성된다. 구동 신호는 선택된 구동 전극들에 인가되어, 액적을 상기 액적의 형상이 더 낮은 에너지 상태의 액적 형상과 비교하여 변형되는 에너지 수득 상태(energised state)에 놓고, 2개의 액적을 근접시킨다. 그 후에, 구동 신호는 액적의 에너지를 더 낮은 에너지 상태로 낮추도록 변해서, 액적은 갭 내로 이완되고, 2개의 액적은 서로 접촉함으로써 액적 계면을 형성한다. 소자에서 감지 전극의 사용은 액적 계면을 가로질러 전기 전류 측정을 가능하게 한다. 감지 전극은 (i) 액적 구동 동안 기준 신호를 인가하거나, (ii) 전기 전류 측정을 기록하기 위해 사용될 수 있다. An electro-wetting device for taking measurements across a droplet interface comprises: a first substrate supporting an array of actuation electrodes; an insulator layer covering said actuation electrodes and having a hydrophobic surface; and a second substrate supporting at least one set of at least two sensor electrodes. The electro-wetting device receives a fluid medium disposed between the substrates, in which droplets of liquid are suspended in the fluid medium. The actuation electrodes receive actuation signals for electro-wetting, moving, and/or modifying the shape of the droplets to form a system of droplets having a droplet interface between droplets. The sensor electrodes make electrical contact with respective droplets in the system of droplets.